The network contract: an instrument to contrast labour exploitation in agriculture. The Italian case - Cangemi, Vincenzo; Pettinelli, Roberto (Italian Labour Law e-Journal, 2021)
The essay, after investigating the criticalities of the agro-food chain that make illegal gang-master trade (“caporalato”) a phenomenon coessential to the survival of the agricultural enterprise on the market in the face of the negotiating dominance of the large-scale retail trade (GDO), , illustrates the prospects and potentialities of the use of the network contract as a tool to contrast the informal economy. The co-determination, in fact, allowing companies to share the cost of labor in return for a joint employment, seems a tool susceptible to combat the serious labor exploitation much more than the criminal sanction policies, even in light of the low effectiveness of the Network of agricultural labor quality.